Evaluación de un pigmento comercial a diferentes edades en pollo de carne en el cantón Chaguarpamba de la provincia de Loja - Campoverde Gordillo, Gabriela Elizabeth (2020)
In the present investigation, a commercial pigment was evaluated at different ages in meat chickens in the Chaguarpamba province of Loja, located at 800 meters above sea level. The experimental design was completely randomized, with 300 boiler chickens of the Cobb 500 line, distributed in three treatments, each experimental unit consisting of 5 repetitions, with 20 animals. Treatment one consisted of supplying pigment at 8 days of age with diets that covered the recommended requirements for the genetic line. In treatment two, pigment was applied to their 15- 42 day rations. In treatment three, pigment was provided at 21-42 days of age. The results determine that the color of the tartars at the pigmentation level did not exist statistical difference in the purchase in each one of the treatments with values between 105 and 106 for tartars in the DSM range, In abdominal fat was low due to the presence of high levels of fiber during the initial 28 days of the present study, in the increase of weight there were not statistical differences between treatments being a little low with respect to the standard of cobb 500 by the presence of high levels in fiber especially the first week and in yield The treatment three was the greater one with the addition of pigment as of the 21 days of age, since it diminished the costs of the inclusion of pigments in early stages. The conclusion was that pigment does not improve the presentation of the carcass at an early age, thus increasing production costs.